Evaluation of Hormone-Induced Stress Responses Using Endogenous Cortisol in Carp (Cyprinus carpio) - I. Berezina , Daria; L. Fomina, Lyubov (KnE Life Sciences, 2021)
With stress studies in fish it is often difficult to determine the degree of response to various stressors, and the interpretation of this influence is usually based on an increase in endogenous cortisol levels. Simulation of stress with synthetic corticosteroids is widely used in ichthyological practice, which raises the question of whether endogenous cortisol is the most appropriate parameter for measuring stress levels in such studies. This work presents the dynamics of the plasma cortisol level in simulating acute and chronic stress in 24 carps by a single injection of dexamethasone in the first experimental group and betamethasone in the second experimental group, in comparison with the control group (without injection) for 21 days. The analysis was performed before injection, as well as after 7, 14 and 21 days of treatment. The hormonal response was compared with that of fish stressed by natural factors (hypoxia). It was found that betamethasone inactivates the production of endogenous cortisol during all subsequent days of the experiment after injection from 353.68±66.39 ng/ml to 7.28±1.27 ng/ml by day 21, while the effect of dexamethasone caused multidirectional fluctuations in its level: from 346.25±43.16 ng/ml to 242.25±58.49 ng/ml on the 7th day, 388.25±37.51 ng/ml on the 14th day and 264.25±21.21 ng/ml on day 21 compared with smooth dynamics in control fish: 376.25±44.04 ng/ml, 366.75±42.82 ng/ml, 335.33±8.57 ng/ml and 366.00±89.22 ng/ml, respectively. It was concluded that measuring the level of endogenous cortisol is not recommended when assessing the degree of stress imitation by these hormones, and in studies of this type it is necessary to search for other indicators. Keywords: carp, cortisol, stress, dexamethasone, betamethasone, hormone